Estimating the proportion of metabolic health outcomes attributable to obesity: a cross-sectional exploration of body mass index and waist circumference combinations. Issue 1 (December 2016) - Tanamas, Stephanie; Permatahati, Viandini; Ng, Winda; Backholer, Kathryn; Wolfe, Rory; Shaw, Jonathan; Peeters, Anna
Abstract Background Recent evidence suggests that a substantial subgroup of the population who have a high-risk waist circumference (WC) do not have an obese body mass index (BMI). This study aimed to explore whether including those with a non-obese BMI but high risk WC as 'obese' improves prediction of adiposity-related metabolic outcomes. Methods Eleven thousand, two hundred forty-seven participants were recruited. Height, weight and WC were measured. Ten thousand, six hundred fifty-nine participants with complete data were included. Adiposity categories were defined as: BMIN /WCN, BMIN /WCO, BMIO /WCN, and BMIO /WCO (N = non-obese and O = obese). Population attributable fraction, area under the receiver operating characteristic curve (AUC), and odds ratios (OR) were calculated. Results Participants were on average 48 years old and 50 % were men. The proportions of BMIN /WCN, BMIN /WCO, BMIO /WCN and BMIO /WCO were 68, 12, 2 and 18 %, respectively. A lower proportion of diabetes was attributable to obesity defined using BMI alone compared to BMI and WC combined (32 % vs 47 %). AUC for diabetes was also lower when obesity was defined using BMI alone (0.62 vs 0.66). Similar results were observed for all outcomes. The odds for hypertension, dyslipidaemia, diabetes and CVD were increased for those with BMIN /WCO (OR range 1.8–2.7) and BMIO /WCO (OR 1.9–4.9) compared to those with BMIN /WCN . Conclusions Current population monitoring, assessing obesity by BMI only, misses a proportion of the population who are at increased health risk through excess adiposity. Improved identification of those at increased health risk needs to be considered for better prioritisation of policy and resources.